Tayma, Saudi-Arabien. Interdisziplinäre Untersuchungen von Räuchergefäßen zur Rekonstruktion antiker Gerüche. Die Arbeiten der Jahr 2016 bis 2018 - Huber, Barbara; Hausleiter, Arnulf; Dinies, Michèle; Christopher, Jan; Säumel, Ina; Pham, Thi Lam Huong (e-Forschungsberichte des DAI, 2018)
Throughout the excavations at the oasis of Tayma, incense burners were discovered showing both traces of burning and residues of burnt aromatics. The multidisciplinary study of these objects aimed at reconstructing the scented world and olfactory landscape of the ancient oasis. By means of LC-ESI-MS/ MS techniques, the characteristic profile of secondary metabolites of resins of Boswellia, Commiphora and Pistacia spp. were detected. The results demonstrate the use different resins in either public, funerary or domestic contexts over more than two millennia (Late Bronze to Late Antiquity). The people of Tayma purchased goods for their own use, which implies that the oasis was not just a transit point on the “Incense Road”, but an active customer.